Pengaruh Minat Belajar dan Kemampuan Pemecahan Masalah Siswa SMP Dengan Model Pembelajaran Berbasis Masalah Menggunakan Software Geogebra Pada Materi SPLDV - Belva Laila Falah Sukri Belva; Jailani (Postgraduate, University of Mataram, 2023)
One of the reasons students struggle to solve mathematical issues is that they are not interested in learning the subject because they believe there are too many formulae to master. Due to this, it is important to have media available when learning mathematics to encourage student’s interest in the subject. This study aims to determine the effect of learning using Geogebra software on problem-solving abilities and interest in learning SPLDV material in class VIII MTs Darul 'Ulum Yogyakarta. The data collection technique used in this research is a questionnaire instrument and problem-solving ability test questions. Data analysis techniques in this study used normality tests, homogeneity tests, and hypothesis testing. The sample used in this study was class VIII MTs Darul 'Ulum Yogyakarta with a total of 20 students. The results of this study showed that learning using Geogebra software affected students' problem-solving abilities and interest in learning mathematics for class VIII students at MTs Darul 'Ulum Yogyakarta